Syi’ir dalam Ihya’ Ulum Al-Din: Membaca Pemikiran Al-Ghazali Melalui Lensa Hegemoni Gramsci - Hamdy, Mohammad Zainal; Soimah, Wurrotus (Sekolah Tinggi Agama Islam Darul Ulum Banyuanyar, Pamekasan, 2025)
This study examines the theme of love in Al-Ghazali's poetry found in Ihya’ Ulum al-Din using Antonio Gramsci's theory of hegemony. The central issue addressed is how these poems represent love not merely as an emotional expression, but as a spiritual force that plays a role in shaping the collective consciousness of Islamic society. The aim of this research is to uncover how the concept of love in Al-Ghazali’s work contributes to the construction of hegemonic Islamic ideologies and values of his time. The study employs a qualitative method with textual and socio-cultural analysis, allowing for an in-depth exploration of the meanings and social functions of the poetry. The findings reveal that Al-Ghazali’s poems on love serve as ideological instruments that reinforce the hegemony of Islamic spiritual values while also offering criticism of deviant religious practices. The contribution of this research lies in its insights into the role of literature—particularly Sufi poetry—in the process of cultural and spiritual hegemony, and its relevance for understanding the concept of love within both religious and contemporary social contexts